Three-dimensional bioprinted BMSCs-laden highly adhesive artificial periosteum containing gelatin-dopamine and graphene oxide nanosheets promoting bone defect repair. (10th February 2023) - Sun, Xin; Yang, Jin; Ma, Jie; Wang, Tianchang; Zhao, Xue; Zhu, Dan; Jin, Wenjie; Zhang, Kai; Sun, Xuzhou; Shen, Yuling; Xie, Neng; Yang, Fei; et al.
Abstract: The periosteum is a connective tissue membrane adhering to the surface of bone tissue that primarily provides nutrients and regulates osteogenesis during bone development and injury healing. However, building an artificial periosteum with good adhesion properties and satisfactory osteogenesis for bone defect repair remains a challenge, especially using three-dimensional (3D) bioprinting. In this study, dopamine was first grafted onto the molecular chain of gelatin using N -(3-dimethylaminopropyl)- N ′-ethylcarbodiimide hydrochloride and N -hydroxysuccinimide (NHS) to activate the carboxyl group and produce modified gelatin-dopamine (GelDA). Next, a methacrylated gelatin, methacrylated silk fibroin, GelDA, and graphene oxide nanosheet composite bioink loaded with bone marrow mesenchymal stem cells was prepared and used for bioprinting. The physicochemical properties, biocompatibility, and osteogenic roles of the bioink and 3D bioprinted artificial periosteum were then systematically evaluated. The results showed that the developed bioink showed good thermosensitivity and printability and could be used to build 3D bioprinted artificial periosteum with satisfactory cell viability and high adhesion. Finally, the 3D bioprinted artificial periosteum could effectively enhance osteogenesis both in vitro and in vivo . Thus, the developed 3D bioprinted artificial periosteum can prompt new bone formation and provides a promising strategy for bone defect repair.